APPEALING FEATURES OF PARTY GAME USING FALL GUYS: ULTIMATE KNOCKOUT - Thiparpakul, Poom; วงษ์เสรี, สรลักษณ์; พรศาลนุวัฒน์ ตันอริยกุล, ภาวินี (Thai Interdisciplinary and Sustainability Review, 2023)
Party games have been a staple genre of multiplayer gaming since its early history, starting as a simple game played locally and now as an online multiplayer that can be played with anyone worldwide. Even then, the game still attracted a new player base, including both casual and veteran gamers. Using the recently released party game Fall Guys as a model, this paper investigated the feature that makes party games appealing to new players. The game became a hit on the first day it was released, with 76520 players on Steam and is the most downloaded PS Plus game as of August 2020 The paper reviewed the history of the party game genre from its beginning as a game show from the early television era to its current as online multiplayer games with the help of the internet connection and improved computer graphics technology, allowing more creativity in visual art and gameplay design, and the reason why these games were popular was because of their accessibility to a large audience and the ability to play with other players. The methodology of this research was done by creating an online survey that rates six appealing features of the game. The result was that the rating of each feature was close to one another, and the funny character and art design had the highest score followed by the humor of the game and the lowest was being able to play with friends. This suggests that while several features are closely appealing, art and visual design would have been the most appealing ones.